2016
DOI: 10.4103/0253-7176.194917
|View full text |Cite
|
Sign up to set email alerts
|

Suicide in India: Distinct Epidemiological Patterns and Implications

Abstract: Suicide is a societal crisis which also deeply impacts the personal and family realms. Indian suicidal data present distinctive epidemiological patterns when we compare it with the global suicide rates and trends. Higher proportions of young individuals are resorting to suicide compared to any other country in the world, and Indian suicide rates, especially South Indian rates, are one of the highest in the world. In this article, we present various historical aspects and theories of Indian suicide and review o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 35 publications
(41 reference statements)
0
15
2
Order By: Relevance
“…28,29,31 Indian studies on suicide revealed rates up to 82 to 95/100,000 especially in the rural population and in southern India. 32,33 The studies further revealed that suicide rates were higher in younger women with hanging and organophosphorus pesticide consumption as the common methods. Lower socioeconomic status, alcohol abuse, and interpersonal issues were associated with suicide in India.…”
Section: Evidence From Developing Countriesmentioning
confidence: 99%
See 1 more Smart Citation
“…28,29,31 Indian studies on suicide revealed rates up to 82 to 95/100,000 especially in the rural population and in southern India. 32,33 The studies further revealed that suicide rates were higher in younger women with hanging and organophosphorus pesticide consumption as the common methods. Lower socioeconomic status, alcohol abuse, and interpersonal issues were associated with suicide in India.…”
Section: Evidence From Developing Countriesmentioning
confidence: 99%
“…32 Contrasting with western and Southeast Asian literature on suicide, depression was noted in only 3.8% of the suicides in India and was associated with alcohol use disorders, financial and interpersonal issues. 33 Concisely stating, the prevalence, methods, psychiatric morbidity, and risk factors for suicide in LMICs differed from the western population and thus adding value for undertaking the current study in a developing nation such as India.…”
Section: Evidence From Developing Countriesmentioning
confidence: 99%
“…Soaring rates of suicide are a subject of increasing concern in the public discourse as well as for the state in India. Between 2005 and 2015, the national rate of suicide grew by over 17% and remains significantly higher than global averages (Mythri and Ebenezer ). Patterns also suggest variations from typical global demographics.…”
Section: Introductionmentioning
confidence: 97%
“…Until now under section 309, as suicide attempt was a criminal offence, possibly there was underreporting of this figure. 8,9,10,11,12,13,14,15 However now as our Parliament changed the law and therefore we presume our staff to be sympathetic, rather than put these patients under criminal jurisprudence. 16 Only by analysing this patient population, we will be able to know its reasons and possibly construct intelligent interventions to prevent it in future.…”
Section: Introductionmentioning
confidence: 99%